The Effect of Literature Circles on English Skills Among Non-English Majors: A Gender-Based Study - Mutiara Ayu; Zelvia Liska Afriani; Dyah Aminatun (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study investigates the impact of literature circles on English language skill development among non-English major university students, with attention to gender-based differences in outcomes. Sixty students were purposively selected and evenly divided into experimental and control groups, with balanced gender representation. Using a mixed-methods design, data were collected through questionnaires, interviews, and classroom observations. The experimental group participated in literature circles, while the control group received conventional instruction. Quantitative analysis revealed significant improvements in speaking fluency (x̄ = 85), vocabulary acquisition (x̄ = 82), and reading comprehension (x̄ = 87) among students in the experimental group. Qualitative findings showed that female students tended to be more active and reported higher levels of enjoyment, while male students demonstrated increased engagement when assigned specific discussion roles. The collaborative structure of literature circles fostered critical thinking, peer interaction, and learner autonomy. These findings suggest that literature circles are an effective, learner-centered, and gender-responsive method for enhancing communicative competence in EFL classrooms. Structured facilitation and role-based accountability can help equalize participation across genders, supporting more inclusive language learning environments.